Epidermal necrolysis (Stevens–Johnson syndrome and toxic epidermal necrolysis): Historical considerations - Jean-Claude Roujeau (Dermatologica Sinica, 2013)
Objective: To describe the history of toxic epidermal necrolysis, before and after the original report by the British dermatologist Alan Lyell in 1956. Methods: Subjective expert choice of key advances in the comprehension of the nosology, classification, causality, and mechanisms of epidermal necrolysis (EN) over more than a century. Results: Epidermolysis had been reported long before Lyell's paper, but most cases had likely been staphylococcal scalded skin syndrome in children. Concerning non-Staphylococcus EN, confusion with erythema multiforme dissipated and its relation to Stevens–Johnson syndrome was clarified. Tremendous advances were made in understanding the causes and mechanisms, with increased acceleration in the last 10 years. Conclusion: The next decade should be devoted to improve the prevention and management of a disease that is the most terrible form of drug hypersensitivity.